Associations between disordered eating, menstrual dysfunction, and musculoskeletal injury among high school athletes - Thein-Nissenbaum, J. M.; Rauh, M. J.; Carr, K. E.; Loud, K. J.; McGuine, T. A. (Journal of Orthopaedic & Sports Physical Therapy, 2011)
STUDY DESIGN: Retrospective cohort study. OBJECTIVES: To determine the prevalence of, and association between, disordered eating (DE), menstrual dysfunction (MD), and musculoskeletal injury (MI) among high school female athletes. BACKGROUND: Female athlete triad (Triad) syndrome is the interrelatedness of DE, MD, and low bone mass. Few studies have examined 2 or more Triad components simultaneously, or their relationship to injury, among female high school athletes. METHODS: The subject sample consisted of 311 female high school athletes competing on 33 interscholastic high school teams during the 2006-2007 school year. Athletes completed the Eating Disorder Examination Questionnaire (EDE-Q) and Healthy Wisconsin High School Female Athletes Survey (HWHSFAS). Athletes were classified by sport type as aesthetic (AES), endurance (END), or team/anaerobic (T/A). RESULTS: Of those surveyed, 35.4% reported DE, 18.8% reported MD, and 65.6% reported sustaining a sports-related musculoskeletal injury during the current sports season. Athletes reporting DE were twice as likely to be injured compared to those reporting normal eating behaviors (odds ratio [OR], 2.3; 95% confidence interval [CI]: 1.4, 4.0). Multivariate logistic regression analyses revealed that athletes who reported a history of DE (OR, 2.1; 95% CI: 1.1, 3.9) or prior injury (OR, 5.1; 95% CI: 2.9, 8.9) were more likely to be injured during the sports season. CONCLUSION: A high prevalence of DE and MD exists among high school female athletes. Additionally, athletes with DE were over 2 times more likely to sustain a sports-related injury during a sports season. Screening and intervention programs designed to identify and decrease the prevalence of DE should be implemented with high school females. LEVEL OF EVIDENCE: Prognosis, level 2b